Simultaneous Quantification of Indium and Nitrogen Concentration in InGaNAs Using HAADF-STEM. (30th September 2014) - Grieb, Tim; Müller, Knut; Cadel, Emmanuel; Beyer, Andreas; Schowalter, Marco; Talbot, Etienne; Volz, Kerstin; Rosenauer, Andreas
Abstract To unambiguously evaluate the indium and nitrogen concentrations in InxGa1−xNyAs1−y, two independent sources of information must be obtained experimentally. Based on high-resolution scanning transmission electron microscopy (STEM) images taken with a high-angle annular dark-field (HAADF) detector the strain state of the InGaNAs quantum well is determined as well as its characteristic HAADF-scattering intensity. The strain state is evaluated by applying elasticity theory and the HAADF intensity is used for a comparison with multislice simulations. The combination of both allows for determination of the chemical composition where the results are in accordance with X-ray diffraction measurements, three-dimensional atom probe tomography, and further transmission electron microscopy analysis. The HAADF-STEM evaluation was used to investigate the influence of As-stabilized annealing on the InGaNAs/GaAs sample. Photoluminescence measurements show an annealing-induced blue shift of the emission wavelength. The chemical analysis precludes an elemental diffusion as origin of the energy shift—instead the results are in agreement with a model based on an annealing-induced redistribution of the atomic next-neighbor configuration.